The antipsychotic story: changes in prescriptions and overdose without better safety. (15th April 2016) - Berling, Ingrid; Buckley, Nicholas A.; Isbister, Geoffrey K.
Abstract : Aims: Morbidity and mortality from drug overdose has decreased over three decades. This is credited to safer drugs and therefore better outcomes in overdose. We aimed to investigate changing prescriptions of antipsychotic medications and associated changes in antipsychotic overdoses over a 26‐year period. Methods: All antipsychotic poisoning presentations to a tertiary referral toxicology unit between 1987 and 2012 were reviewed. Data were collected prospectively on demographics, ingestion information, clinical effects, complications and treatment. Rates of antipsychotic drug use in Australia were obtained from Australian government publications for 1990–2011 and linked to overdose admissions by postcode. Results: There were 3180 antipsychotic overdoses: 1235 first generation antipsychotics, 1695 'atypical' second generation antipsychotics and 250 lithium overdoses. Over 26 years, antipsychotic overdoses increased 1.8‐fold, with first generation antipsychotics decreasing to one‐fifth of their peak (≈80/year to 16) and second generation antipsychotics increasing to double this (≈160/year), olanzapine and quetiapine accounting for 78%. All antipsychotic overdoses had a median length of stay of 18.6 h, 15.7% admitted to intensive care unit, 10.4% ventilated and 0.13% died in hospital, which was the same for first generation compared to second generation antipsychotics. There was a 2.3‐fold increase in antipsychotic prescriptions over the same period; first generation antipsychotics declined whereas there was a dramatic rise in second generation antipsychotics, mainly olanzapine, quetiapine and risperidone (79%). Conclusion: Over 26 years there was an increase in antipsychotic prescribing associated with an increase in antipsychotic overdoses. Although the type of antipsychotics changed, the morbidity and mortality remained the same, so that antipsychotics are an increasing proportion of overdose admissions.